Anti‐apoptotic effects of human gingival mesenchymal stromal cells on polymorphonuclear leucocytes. (15th January 2021) - Blufstein, Alice; Behm, Christian; Kubin, Barbara; Gahn, Johannes; Moritz, Andreas; Rausch‐Fan, Xiaohui; Andrukhov, Oleh
Abstract: Objectives: Polymorphonuclear leucocytes (PMNs) constitute the first line of host defence and are crucial in maintaining periodontal health. Their survival and function are modulated by mesenchymal stromal cells (MSCs) from different origin. Gingival MSCs (GMSCs) play an important role in maintaining oral health and in the initial inflammatory response. The present study aimed to investigate the effects of GMSCs on PMNs apoptosis and reactive oxygen species (ROS) production. Methods: PMNs were either directly incubated with untreated, interleukin (IL)‐1β‐ or tumour necrosis factor (TNF)‐α‐treated GMSCs or stimulated with their conditioned media. Resulting ROS production was evaluated by dichlorofluorescin diacetate staining, whereas PMNs apoptosis was assessed by Annexin V staining, followed by flow cytometry analysis. Results: While conditioned media of untreated and TNF‐α‐treated GMSCs did not affect apoptosis of PMNs, it was significantly delayed by conditioned media of GMSCs treated with IL‐1β. In direct co‐culture, GMSCs exerted anti‐apoptotic effects on PMNs independently of the previous stimulation. However, the strongest impact was observed by IL‐1β‐treated GMSCs. ROS production of PMNs was not influenced by GMSCs or their conditioned media. Conclusion: This study demonstrates for the first time the immunomodulatory properties of GMSCs towards PMNs, revealing that IL‐1β enhances anti‐apoptotic effects of GMSCs.